2017
DOI: 10.2147/ndt.s136815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Canon chord progression on brain activity and motivation are dependent on subjective feelings, not the chord progression per se

Abstract: Abstract:A number of studies have indicated that relaxing and pleasant melodies are useful for the treatment of patients with psychiatric disorders, including schizophrenia, depression, and dementia. However, few studies have investigated what constitutive elements of the music had an effect on brain activity. As Canon chord progression is one of critical elements for pleasant melodies, we sought to examine the effects of Canon chord progression and pitch-shifted Canon chord progression on brain activity using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Music elicited a greater frontocentral P300 response (400-500 ms) than emotional vocalizations, while words elicited a larger centroparietal N400 amplitude than music. These findings is consistent with the previous literature reporting larger P300 amplitudes over frontal areas in response to pleasant vs. unpleasant music (Kayashima et al, 2017).…”
Section: Auditory Perceptionsupporting
confidence: 93%
“…Music elicited a greater frontocentral P300 response (400-500 ms) than emotional vocalizations, while words elicited a larger centroparietal N400 amplitude than music. These findings is consistent with the previous literature reporting larger P300 amplitudes over frontal areas in response to pleasant vs. unpleasant music (Kayashima et al, 2017).…”
Section: Auditory Perceptionsupporting
confidence: 93%
“…Active g.LADYbird electrodes were placed on Fz, Cz, T7 and T8. The reason for selecting Fz was that it is shown that Fz has the highest average amplitude of responses in subjects to whom a music is pleasant (Kayashima et al, 2017). Three other channels were consistently used in a number of previous ASSR studies (Lopez et al, 2009;Higashi et al, 2011;Kim et al, 2011;Heo et al, 2017;Shamsi et al, 2017).…”
Section: Experiments Apparatus and Recording Insert Earphones Er-3a (mentioning
confidence: 99%